2020
DOI: 10.1155/2020/9573950
|View full text |Cite
|
Sign up to set email alerts
|

Looking into the Content of the Canadian Occupational Performance Measure (COPM): A Danish Cross-Sectional Study

Abstract: Purpose. To examine the content validity of the Danish version of the Canadian Occupational Performance Measure (COPM-DK). Materials and Methods. This cross-sectional study was performed in a hospital and a community rehabilitation centre. The content validity of the COPM was assessed by relating the clients’ prioritized occupational performance issues (OPIs) to the conceptual model of the Canadian Model of Occupational Performance and Engagement (CMOP-E) and the levels of the Taxonomic Code of Occupational Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The data in this study were collected as part of the overall cross-cultural validation process of the COPM-DK, in which all clients were offered intervention. Details of study flow and the overall design can be found in the papers on the COPM-DK’s validity (Enemark Larsen et al 2020c; 2020a) and reliability (Enemark Larsen et al 2020b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data in this study were collected as part of the overall cross-cultural validation process of the COPM-DK, in which all clients were offered intervention. Details of study flow and the overall design can be found in the papers on the COPM-DK’s validity (Enemark Larsen et al 2020c; 2020a) and reliability (Enemark Larsen et al 2020b).…”
Section: Methodsmentioning
confidence: 99%
“…However, as former versions were never examined for cross-cultural validity, this process was initiated in 2015 with a new translation, the COPM-DK (Enemark Larsen et al 2019a). Since then, the COPM-DK’s utility (Enemark Larsen et al 2019b), validity (Enemark Larsen et al 2020c; 2020a) and reliability (Enemark Larsen et al 2020b) have been found adequate. Now the intent of this study was to examine the responsiveness of the COPM-DK in a group of clients from different parts of Danish health care who all had an intervention.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The authors grouped the individualized COPM goals at baseline into 10 themes 1 . However, in the conceptual understanding of the COPM, issues of occupational performance are identified based on the Canadian Model of Occupational Performance and Engagement (CMOP‐E) 2,3,5 . Problems with performance components, related to tasks or body functions, are not the focus here.…”
mentioning
confidence: 99%
“…Problems with performance components, related to tasks or body functions, are not the focus here. Themes like stairs, jumping, and gross motor skill may go beyond the measurement's content validity, nevertheless identifying lower‐level OPIs is a common misconception 3,5 . This is possibly caused by using an obsolete edition of the COPM manual, in which so‐called OPIs at lower levels than occupation were included 3,5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation